A CONTRASTIVE ANALYSIS OF NOUN FORMATION IN MALAY AND ENGLISH - Agus, Sitti Hasmah; Ramdayani, Sri; Mujaddidah, Husnul (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2025)
This study conducts a contrastive analysis of noun formation in Malay and English, focusing specifically on affixation processes. The research aims to identify and describe the types of affixes used in forming nouns in both languages, including prefixes, suffixes, infixes, and confixes, and to examine the similarities and differences between the two morphological systems. A descriptive qualitative design was applied, with data collected from written texts, including books and magazines in both Malay and English. The data were analyzed by classifying affixed words according to affix type and examining their morphological functions in noun formation. The findings reveal that both Malay and English utilize affixation in noun formation, with some shared meanings despite different forms. Malay employs prefixes, suffixes, infixes, and confixes, while English primarily uses prefixes and suffixes. Affix variation in English occurs mainly in suffixes, whereas in Malay it occurs predominantly in prefixes. The effects on base words also differ: English noun formation involves both letter mutation and omission, while Malay mainly involves mutation. Formation patterns vary according to the types of base words in each language. This study contributes to the field of morphology and contrastive linguistics by providing a systematic comparison between two languages from different language families. The findings are valuable for language learners, particularly those with a Malay background studying English, as understanding these structural differences can enhance morphological awareness and support vocabulary development.